Liposomal and Lipid-Based Drug Delivery Systems: Bridging Gut Microbiota and Pediatric Disorder Treatments - Raluca Ioana Teleanu; Elena-Theodora Moldoveanu; Adelina-Gabriela Niculescu; Elena Predescu; Eugenia Roza; Iulia Florentina Tincu; Alexandru Mihai Grumezescu; Daniel Mihai Teleanu (Pharmaceutics)
The intestine is an important segment of the gastrointestinal tract, which is involved in complex processes that maintain the body’s normal homeostasis. It hosts a vast, diverse, and dynamic microbial community called the gut microbiota, which develops from birth. It has been observed that the gut microbiota is involved in essential physiological processes, including the development of the central nervous system via the gut microbiota–brain axis. An alteration of the gut microbiota can lead to serious health problems, including defective neurodevelopment. Thus, this paper aims to highlight the most recent advances in studies that focus on the link between the gut microbiota and the evolution of neurodevelopmental diseases in children. Currently, studies show that the use of drugs that stimulate and restore the gut microbiota (e.g., probiotics and prebiotics) have the potential to alleviate some of the symptoms associated with conditions such as Autism Spectrum Disorder, Attention Deficit Hyperactivity Disorder, Tic Disorder, Tourette Syndrome, epilepsy, and Down Syndrome. In addition, due to the challenges associated with drug administration in children, as well as the widespread shortage of medications intended for pediatric use, researchers are working on the development of new delivery systems. Liposome-based systems or solid lipid nanoparticles have been safely used for drug delivery in various pediatric conditions, which may also indicate their potential for use in the administration of microbiota-modulating therapies.